What to read and why - Prose, Francine, 1947- (Harper, an imprint of HarperCollinsPublishers, 2018)
Celebrates the pleasures of reading and pays homage to the works and writers the author admires above all others, from Jane Austen to Charles Dickens to Jennifer Egan.